The individual And directions Poetic romance In Andalusia in the fifth and sixth centuries of migration - فارس, عيسى; جمعة, وفاء; علي, أحمد (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The research attempts to discern the visions that bear subjective tendencies, and to identify the perceptions transmitted in the texts that he followed in Andalusian poetry to understand the life orbit of the individual human being. The research committed to trying to discover the power of the poetic self, and its presence in the poetic text, based on romantic trends that adopt the new viewpoint in Andalusian poetry. The poetic evidence carried multiple tracks of romantic individual tendencies Search placed it in two addresses: The poet's self and the discourse of the other The totalitarian self The study adopts a plan based on placing the every title in a general space for understanding to define the foundations of each title within the general understanding of the individual level and its presence in the poetic text, Because the extent to which we feel the power of the poetic self expressing the individual determines the extent to which Andalusian poetry has approached romantic trends, and It helps to locate it between the classical approach that we have referred to, and the romantic orientations, based on a necessary parallel to the temporal and spatial construction.